Investigation of the sqr and fcc Genes Associated with the Sulfur Oxidation Activity of a Rhodobacter capsulatus Strain Isolated in Vietnam - Phuc, Do Thi; Phuong, Nguyen Minh; Hai, Pham The; Anh, Tran Thi Thuy; Thao, Nguyen Ha Phuong; Anh, Do Thi Tram; Yen, Pham Bao (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4, 2025)
Flavoproteins s ulfide:quinone oxidoreductase (SQR) and flavocytochrome c sulfide dehydrogenase (FCC) , two key enzymes involved in the sulfide oxidation pathways, are responsible for the hydrogen sulfide (H 2 S)- metabolizing capability of various bacterial strains employed in the biological treatments of the toxic gas H 2 S. Previous studies mainly focus on the isolation of sulfur-oxidizing bacteria (SOB) and the evaluation of the total sulfur oxidation activity. Thus , in this study , an in - depth investigation of the sqr , fcc genes , the encoded proteins , and their association with the sulfide oxidation activity in a SOB bacterial s train , Rhodobacter capsulatus , was carried out . Firstly , t he specific primers were designed and used to amplify sqr and fcc genes of a Rhodobacter capsulatus strain isolated in Vietnam. In addition , the bacterial cells were fractionated to obta in periplasmic, membrane, and cytoplasmic fractions for denaturing SDS-PAGE analysis and activity assay . On the SDS-PAGE gel, the bands corresponding to the calculated molecular weights of SQR ( approximately 47 kDa in the membrane fraction) and FCC (approximately 35 kDa in the periplasmic fraction) could be observed. S ignificant sulfide oxidation activity could be detected in the periplasmic and the membrane fractions compared to the cytoplasmic fraction (2 and 20 times higher , respectively ) . More importantly, sulfide oxidation activit ies in these fractions were inhibited by the specific flavoprotein inhibitor KCN, indicating possible association of SQR and FCC with the recorded activity. T he study has initially established the evidence supporting the link between the presence of sqr , fcc -encoded proteins and the sulfide oxidation activity in the studied R. capsulatus bacterial s train for further research utilizing SOB in environmental treatment applications.